2011
DOI: 10.1016/j.jvs.2011.06.094
|View full text |Cite
|
Sign up to set email alerts
|

Women with Peripheral Arterial Disease Experience Faster Functional Decline than Men with Peripheral Arterial Disease

Abstract: ventricular contractility or anti-arrhythmic properties of ␤-blockers. ␤-blockers may also prevent plaque rupture in coronary arteries by reducing mechanical stress on the coronary plaques (Lopez-Sendon J, et.al. Eur Heart J 2004:25:1341 and may decrease circulating levels of C-reactive protein thereby stabilizing coronary plaques through anti inflammatory mechanisms (Jenkins NP, et.al. Am J Med 2002;112:269-74). The duration of ␤-blocker treatment before vascular surgery and its effect on cardiovascular outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…7 More specifically, women with PAD have a higher rate of mobility loss due to poorer lower extremity functioning compared to men. 11,12,13 Moreover, from hospital discharge data from New York, New Jersey, and Florida, Vouyouka et al 14 found that, for women receiving surgical interventions for PAD, mortality rates were substantially higher compared to men after adjusting for co-existing conditions. This lends support for more non-invasive approaches for PAD treatment to reduce pain and increase function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 More specifically, women with PAD have a higher rate of mobility loss due to poorer lower extremity functioning compared to men. 11,12,13 Moreover, from hospital discharge data from New York, New Jersey, and Florida, Vouyouka et al 14 found that, for women receiving surgical interventions for PAD, mortality rates were substantially higher compared to men after adjusting for co-existing conditions. This lends support for more non-invasive approaches for PAD treatment to reduce pain and increase function.…”
Section: Introductionmentioning
confidence: 99%
“…17 Women have a higher rate of mobility loss with PAD due to poorer lower extremity functioning compared to men. [11][12][13] Patients with PAD completing supervised exercise training were found to have a higher level of event-free survival compared to patients who did not. 18,19 Golomb et al 16 support the use of exercise for protecting against coronary artery disease and cerebrovascular disease due to its beneficial effects on the risk factors of insulin resistance, hypertension and dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…It was hypothesized that women have inferior outcomes after SET associated with an accelerated functional decline. 5 …”
mentioning
confidence: 99%
“…[6][7][8][9][10][11] Although not widely recognized by the public or by clinicians, the prevalence and burden of PAD is equal, if not higher, in women compared to men. 2,5,[12][13][14] In addition, women with PAD experience faster functional decline 15 and have poorer outcomes after lower extremity revascularization procedures, compared to men. [16][17][18] Because women have a longer life expectancy than men, women will be even more disproportionately affected with PAD in the future as the population ages.…”
mentioning
confidence: 99%